Critical thinking among college students a cross-cultural study - Paned, Anna Liza De La Cruz (2007)
This study compared the concepts of two different groups of respondents of critical thinking to help find the solutions for some educational issues and to contribute to curricular development. The respondents were grouped according to their nationality, namely, Filipino and German. The schools where they came from are both state universities, and the curriculum used in their respective schools was also considered in the analysis of results in addition to the responses given by each of the respondents. In the course of the study, it was assumed that the results or data gathered will lead to the analysis of some educational concerns and realization of solutions specifically on the cultivation and promotion of critical thinking skills in the concerned institutions and in the society at large.
Thesis (M.A. Philosophy of Education)--University of the Philippines, Diliman.
Keywords: Critical thinking in adolescence; College students -- Philippines